Choice factors for parents selecting independent primary schools in Gauteng (2015)
Ph.D. (Marketing Management) === The ability of independent schools to survive and grow would be enhanced by knowledge of what motivates parents when selecting independent schools in order to assist these schools in better targeting their marketing efforts (McGovern, 2011:16). The primary objective of the study is to recommend marketing guidelines for independent schools and was achieved to identify the choice factors influencing parents’ selection of independent primary schools, identifying the most important choice factors and demographic differences regarding the importance parents attach to choice factors. The external factors influencing the selection of independent schools, the relative importance of price, school facilities and the enrolment process were determined. The usefulness of the sources of information used in the decision-making process was investigated. Both exploratory (qualitative technique) and conclusive (quantitative technique) research designs were followed. For the qualitative technique, dept interviews with ten parents from different independent schools in Gauteng were conducted. For the quantitative technique, a non-probability judgement sample of 669 grade one parents from thirty (30) independent schools in Gauteng participated in the study. The findings of the study identified 29 different choice factors with small class size ranked the highest as choice factor. Previous interactions with the school are the highest ranked external factor influencing the decision-making process of parents and they prefer discount when two or more children from the same household are enrolled. With regard to school facilities, a computer centre is the most important for parents, and a science laboratory is less important. Parents prefer an interview with the principal when enrolling their child and the school open day and school website are the most valuable sources of information for prospective parents. Social media are not considered to be particularly a valuable source of information …